High-performance work system and innovation capabilities: The mediating role of intellectual capital - Hafiz Ali Javed; Naveed Ahmad Khan; Silke Michalk; Noor Ullah Khan; Muhammad Kamran (Administrative Sciences, 2023)
This study examined the effect of high-performance work systems on developing incremental and radical innovation capabilities. Drawing on resource-based and knowledge-based theories, the mediating effects of human capital, social capital, and organizational capital were tested. Data were collected from 233 middle-to-senior level managers working in the banking sector of Pakistan, and hypotheses were tested through partial least squares structural equation modeling using Smart PLS 4.0. The findings showed that all components of intellectual capital mediated the relationship to develop both types of innovation capabilities. In terms of the strength of the relationship, social capital was found to be a more effective mediator, and next to this were human capital and organizational capital, respectively. Our findings contribute to the existing literature by explaining the relationship between HPWS and innovation capabilities, which is also referred to as the black box through the mediation of intellectual capital. Decision makers should recognize the importance of this relationship because it develops innovation capabilities that enhance organizational performance by giving them a competitive advantage.
Keywords: 350; high-performance work system; human capital; incremental innovation capability; organizational capital; radical innovation capability; social capital